2013
DOI: 10.1097/igc.0b013e31827b87b1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Geographic Variations in Treatment on Outcomes in Ovarian Cancer

Abstract: Differences in survival rates for ovarian cancer across British Columbia can be attributed to variations in disease characteristics and treatment, particularly rates of optimal debulking and combination chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…While individual patient-level factors were thought to explain much of the variance, both studies concluded that provider supply could account for many of the geographic differences. In Canada, Dehaeck et al reported a population-based study of ovarian cancer within five health authority regions in the province of British Columbia demonstrating geographic variation in practice patterns in the context of a single-payer, publicly funded health care system [32]. Significant differences were observed across provincial regions for access to a gynecologic oncologist, the rate of optimal debulking, and administration of combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While individual patient-level factors were thought to explain much of the variance, both studies concluded that provider supply could account for many of the geographic differences. In Canada, Dehaeck et al reported a population-based study of ovarian cancer within five health authority regions in the province of British Columbia demonstrating geographic variation in practice patterns in the context of a single-payer, publicly funded health care system [32]. Significant differences were observed across provincial regions for access to a gynecologic oncologist, the rate of optimal debulking, and administration of combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, concentration of services for ovarian cancer care could be an effective means to reduce disparities in treatment and outcomes and promote health equity. Ultimately, all people should be afforded the same standard of care, including access to appropriately qualified surgeons and an optimal treatment setting, regardless of race, SES, or where they reside [32]. …”
Section: Discussionmentioning
confidence: 99%
“…This study is consistent with our findings regarding the importance of type of hospital but did not identify the importance of distance in determining the type of hospital attended. A recent population-based study in British Columbia, 14 which like Australia that has a publically funded health system, also provides indirect evidence for an influence of distance on outcome of ovarian cancer. Examining ovarian cancer survival differences by Health Region, the study found that once disease characteristics (stage and grade) and treatment (optimal debulking and chemotherapy) were taken into account, survival differences previously attributed to health regions were no longer significant.…”
Section: Discussionmentioning
confidence: 99%
“…These differences, particularly the observed variation in chemotherapy practice, prompted this study to evaluate the effect of chemotherapy on overall survival, while accounting for variations in demographics, disease, and treatment. A detailed description of regional differences is the subject of another study, 8 although it is worth noting that the health authority region with the highest mortality (age-adjusted mortality hazards ratio of 1.27 relative to the provincial mean; 95% confidence interval [CI], 1.08Y1.49) had the lowest rate (62.1%) of combination chemotherapy and the highest rate (24.2%) of single-agent carboplatin among all patients eligible for chemotherapy.…”
Section: Resultsmentioning
confidence: 99%